Mode-phase-difference photothermal spectroscopy for gas detection with an anti-resonant hollow-core optical fiber - Pengcheng Zhao (Nature Portfolio, 2020)
Typically, the performance of the state-of-the-art laser sensors is insufficient for many high precision applications. Here, the authors report mode-phase-difference photothermal spectroscopy with a dual-mode anti-resonant hollow-core optical fiber and demonstrate acetylene detection with ultra-high sensitivity.